2011
DOI: 10.1016/j.physa.2011.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Negative emotions boost user activity at BBC forum

Abstract: We present an empirical study of user activity in online BBC discussion forums, measured by the number of posts written by individual debaters and the average sentiment of these posts. Nearly 2.5 million posts from over 18 thousand users were investigated. Scale free distributions were observed for activity in individual discussion threads as well as for overall activity.The number of unique users in a thread normalized by the thread length decays with thread length, suggesting that thread life is sustained by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
130
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(150 citation statements)
references
References 31 publications
11
130
1
1
Order By: Relevance
“…Recently, intensive research based on these empirical data, seen as examples of complex dynamical systems in the physics laboratory, has been performed: this research contributed to quantitative study of social phenomena on Blogs [10,11], Diggs [12], Forums [13], online games [14,15], online social networks MySpace [16], Facebook [17], Twitter [18], online chats [19] and other online communication systems. By using different machine-learning methods of text analysis (a recent review of methods can be found in [20]), one can infer contents that are communicated in the text messages exchanged between users.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, intensive research based on these empirical data, seen as examples of complex dynamical systems in the physics laboratory, has been performed: this research contributed to quantitative study of social phenomena on Blogs [10,11], Diggs [12], Forums [13], online games [14,15], online social networks MySpace [16], Facebook [17], Twitter [18], online chats [19] and other online communication systems. By using different machine-learning methods of text analysis (a recent review of methods can be found in [20]), one can infer contents that are communicated in the text messages exchanged between users.…”
Section: Introductionmentioning
confidence: 99%
“…However, many condemned Swan as a flawed individual, mother and wife; sanctioned the "public policing of pregnant women"; and reinforced negative attitudes towards pregnant women who smoke. 6 While the malicious nature of many comments directed at Swan may be indicative of the negative and, at times, abusive environment of online forums in general 32 , a coherent public health response could have appealed for more understanding of Swan's struggle with quitting smoking. This response could have provided accurate smoking and health information, and important advice and information to support quitting.…”
Section: Discussionmentioning
confidence: 99%
“…The views gathered were from self-selecting individuals who were unlikely to be representative of the Australian population. Further, it has been reported that negative emotions motivate people to express their opinions and the most active people who post online comments are those with negative views on events 40 . It was not clear within the published paper whether commentators were posting more than once 33 .…”
Section: Purchasing Behaviour (Intended)mentioning
confidence: 99%